English Camp Enjoyable Learning: Pendampingan Program Pembelajaran Bahasa Inggris untuk Siswa MA Al-Asy'ari Keras Diwek Jombang - Islam, Aang Fatihul; Ni'amah, Afi; Fatin, Devi Latifah (Jurnal Ilmiah Pangabdhi, 2024)
This activity aims to provide training and assistance for English language learning programs outside class hours using a hybrid learning approach. This community service takes the form of assisting an English language club in the form of an English Corner to become a forum for learning English which will later become one of the school's extra-curricular activities. The results of the achievements of ECEL participants during the training program both in terms of cognitive and skills are in line with expectations, namely (1) participants are able to understand the ECEL program material by 95%, (2) participants are able to practice speaking English with the ECEL learning model by 85%, (3) participants stated that the ECEL program could be applied to students learning to speak English (speaking) as much as 100%, (4) participants stated that the learning module designed by the Abdimas team could be applied to the ECEL program as much as 99% and (5) participants felt that the program ECEL is effective, fun and we hope that in the following years 95% more activities like this program will be held.